Economic analysis of trypanocide use in villages under risk of drug resistance in West Africa. - Affognon, Hippolyte D. (University of Hannover, 2007)
Economic analysis can assist in the understanding of the factors that determine the success of trypanosomosis control by cattle farmers in the cotton zone of West Africa. Trypanocides are the most widely used method of control, and determining their short- and long-term productivity provides important information. However, this must be interpreted in the light of emerging drug resistance, which poses a major obstacle to the sustainability of drug use. More generally, this research aims to advance the methodology of measuring the productivity of animal disease control inputs in West African cattle production. The study includes an empirical assessment of the productivity of trypanocidal drugs and the costs of trypanosomosis under village conditions. The analysis was extended to capture the implications for the livelihood of the poor cattle farmers of a declining susceptibility of trypanosomes to drugs. The results of this research can help decisionmakers to put in place strategies for improved management of trypanosomosis and trypanocidal drug resistance. The study was conducted in Burkina Faso and Mali from June 2003 to May 2004. Data were collected by a team of veterinary epidemiologists, technicians and agro-economists. In all, 206 herds with a total of 3565 cattle in eighteen villages were monitored during a period of twelve months. Input and output data were collected by enumerators posted in villages for which epidemiological conditions were assessed throughout the study period. Additional price information was collected in local markets, abattoirs and through focus group discussions. It was found that cattle-keeping is important in both Mali and Burkina Faso; however, herds were larger in Mali. The smaller herd size in the study area compared to other parts of sub-Saharan Africa and the higher ratio of draught animals to male adult cattle, especially in Burkina Faso, indicate a farming system more oriented towards intensive use of draught animals in crop production. The majority of cattle farmers in the study area considered trypanosomosis the most important disease of cattle, and knowledge of the cause of trypanosomosis in the study zone was relatively high compared to other parts of sub-Saharan Africa. Farmers are aware of many strategies to control the disease. However, their preferred strategy is the use of trypanocidal drugs and the majority of treatments are given by cattle farmers, although this is not legal. In the methodology developed, livestock production is modelled as a process in which local resources and external inputs are used to generate multiple outputs such as milk, meat, draught power, and manure, and indirect outputs including the finance and insurance functions of maintaining cattle stocks. The study applies a production function framework and integrates a damage control function to quantify cattle production output losses as well as the productivity effect of trypanocide use under different epidemiological conditions. For the estimation of the productivity of disease control inputs, a conventional Cobb-Douglas production function and a modified Cobb-Douglas function that integrates a damage abatement function were specified. Dummy variables were used to capture the effects of disease prevalence and drug resistance, thus taking into account different epidemiological conditions. Three different specifications of the exponential damage control function were tested. The specification that includes two sources of damage from diseases provided the best fit and was used for comparison with the Cobb-Douglas production function in the analysis. The productivity estimates of trypanocides in this study show that the damage control function provides consistently higher marginal productivity for both trypanocides (isometamidium and diminazene aceturate) in cattle production systems where disease is common and isometamidium resistance is high. However, the conventional Cobb-Douglas production function model shows that the productivity of trypanocidal drugs decreases in the situation where trypanosomosis disease prevalence and drug resistance are both high. The results suggest that treating the damage control inputs such as trypanocides in cattle production, as yieldincreasing inputs in the conventional framework is likely to generate misleading results. The marginal value products of isometamidium in all epidemiological conditions, and the marginal value product of diminazene in high-prevalence-high-resistance conditions, reveal an underuse of trypanocidal drugs. In a strict economic interpretation, this implies that in the short term cattle farmers could increase the profitability in those conditions if they increase trypanocide input beyond current levels. On the other hand, the static analysis applied in this study does not take into account the negative externality of trypanocide resistance in the future. If the use of trypanocide increases, cattle farmers will also be more likely to experience future losses from trypanocide resistance. To delay and even reverse the development of resistance the concept of “rational drug use” is recommended. Using drugs rationally entails: reducing need for drugs by disease prevention strategies; decreasing use of drugs by replacing with alternatives; ensuring drugs are given only when clinically needed; giving the appropriate drug at the appropriate dose; and ensuring correct administration of the drug. This study confirms that trypanosomosis is an important disease in the cotton zone of West Africa. Although drug resistance is increasing, trypanocidal drugs used are still effective against the disease. However, at the current sub-optimal level of isometamidium use, output losses are much higher – 9.8% to 22.7% of the value of output – than in a situation where isometamidium use is optimal for the epidemiological conditions. When disease control effort reaches the optimum level, output losses are much lower in all epidemiological conditions (1.3% to 1.5% of output). At the current use of trypanocidal drugs, economic losses due to trypanosomosis range from €9.50 to €22.00 per TLU1 and year. The costs of trypanosomosis at the current level of disease control effort, which include the control costs and the remaining loss after control are higher than they would be if isometamidium use was at optimal levels, in all epidemiological conditions. Currently, trypanosomosis disease costs cattle farmers €13.30 to €26.00 per TLU and year; however, at optimal disease control efforts, costs would be reduced to €8.60 to €10.10 per TLU and year, depending on epidemiological conditions. While the current costs of the disease represent on average 12% to 28% of the output derived from cattle production in the study area, costs of the disease at optimal drug usage would represent only 7% to 8% of output depending on disease prevalence and drug resistance levels. Lower costs of the disease and the increasing productivity of trypanocide in conditions of high drug resistance may create an intractable situation in which cattle farmers’ choices for trypanosomosis control measures are guided by the phenomenon of path dependency. Once this occurs, the only options for controlling the disease would be the discovery of new drugs, for which the development is prohibitively expensive, or eradication of the tsetse vector of trypanosomosis – a strategy that has never been sustainable without considerable external support. Maintaining the effectiveness of trypanocides is hence a priority for farming systems in West Africa. The study has demonstrated the feasibility of applying the damage control framework for measuring the productivity of animal disease control inputs at farm level in poor African countries. The model developed here concentrates on the direct effects of the disease, while the dynamic aspects of drug resistance are included in the model a simplified manner only. To capture these dynamic processes further research is required for example to develop a bioeconomic model that integrates the impacts of trypanosomosis on cattle farmers’ livelihoods and adequately captures the biological process of drug resistance.